Chapter Power and Maintenance in the Alpine Middle Ages - Leggero, Roberto (Taylor & Francis, 2024)
This interdisciplinary volume focuses on the politics, economics, technologies, uses, and cultures of maintenance of different forms of communication over long time or in Longue Durée. Throughout the chapters, contributors from a wide range of fields explore transversal and trans-temporal issues of communication maintenance. Among these are the struggles to keep communication infrastructures functioning, the hidden work of maintenance done by both experts and non-experts such as everyday users, the political significance of maintaining communications (or not maintaining them), and the different habits and significance of maintenance in different times and world regions. The forms of communication covered include broadcasting, telecommunications such as the telegraph and telephone, digital and popular media as computers and mobile phones, mostly forgotten media like pneumatic tubes, transportation infrastructures, maps as used as tools to politically control land, the clock as a medium and a material artifact, and many more. This book will be of interest to students and scholars of communication and media studies, the history of science and technology, general history, geography, maintenance studies, and other related disciplines.